Kinematic Rupture Process of Manyas (Mw=4.7) and Gemlik (Mw=4.8) Earthquakes Occurred in The Southern Marmara Region - Feyza Nur Bekler; Nurcan Meral Özel; Gülüm Tanırcan (Doğal Afetler ve Çevre Dergisi)
Source characterization and slip history were estimated for two moderate-sized earthquakes which occurred on the southern branch of the North Anatolian Fault zone (NAFz): October 20, 2006 (Mw 4.7) Manyas Earthquake and October 24, 2006 (Mw 4.8) Gulf of Gemlik Earthquake. These events are the largest to have occurred in the last 20 years on the southern branch of the NAFz. Multi time-window linear waveform inversion technique (MTWIT) was applied to strong ground motion (SGM) data. Theoretical Green’s functions between subfaults and stations were calculated by a Discrete Wave Number Method (DWNM) using one-dimensional (1-D) velocity structure. The inversion technique used in this study yields a non-unique solution. Therefore, various rupture models were tested until a satisfactory match was obtained between observed and synthetic data. Results showed simple patterns in slip distributions. Max. slips are 0.18 m and 0.12 m and seismic moments are 3.43E+15 Nm and 1.73E+15 Nm for the Gemlik and Manyas Earthquakes, respectively. Results were compared with those of similar sized earthquakes around the world and a new empirical relationship was proposed between seismic moment and rupture area. It was aimed at providing useful information for resolving rupture mechanisms and triggering of the events in Southern Marmara region through the findings of the present study.